2024
DOI: 10.1111/epi.17910
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and the risk of COVID‐19‐related hospitalization and death: A population study

Huw Strafford,
Joe Hollinghurst,
Arron S. Lacey
et al.

Abstract: ObjectivePeople with epilepsy (PWE) may be at an increased risk of severe COVID‐19. It is important to characterize this risk to inform PWE and for future health and care planning. We assessed whether PWE were at higher risk of being hospitalized with, or dying from, COVID‐19.MethodsWe performed a retrospective cohort study using linked, population‐scale, anonymized electronic health records from the SAIL (Secure Anonymised Information Linkage) databank. This includes hospital admission and demographic data fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
(56 reference statements)
0
3
1
Order By: Relevance
“…Moreover, we found that having a diagnosis of epilepsy/seizure or headache carried a lower risk of death in multivariable analyses. This is different from prior studies that found an increased risk of death among people with epilepsy and COVID-19 infection compared to people without COVID-19 (a hazard ratio of 2.15 [95% CI 1.78–2.59]) ( 21 ). However, two other studies did not demonstrate an increased risk of in-hospital death among people with epilepsy and COVID-19 infection ( 22 , 23 ).…”
Section: Discussioncontrasting
confidence: 92%
“…Moreover, we found that having a diagnosis of epilepsy/seizure or headache carried a lower risk of death in multivariable analyses. This is different from prior studies that found an increased risk of death among people with epilepsy and COVID-19 infection compared to people without COVID-19 (a hazard ratio of 2.15 [95% CI 1.78–2.59]) ( 21 ). However, two other studies did not demonstrate an increased risk of in-hospital death among people with epilepsy and COVID-19 infection ( 22 , 23 ).…”
Section: Discussioncontrasting
confidence: 92%
“…As part of the COVID-19 and Epilepsy in Wales (CoVEW) project, we have previously shown an increased COVID-19 vaccine uptake in PWE and a small increased risk of COVID-19 hospitalizations and deaths for PWE in Wales. 6,17 In a previous study on epilepsy deaths at the beginning of the pandemic (to the end of 2020), we found When removing COVID deaths, RRs were .88 (95% CI = .81-.95) and 1.29 (95% CI = 1.08-1.53). Status epilepticus rates did not change significantly during the pandemic (RR = .95, 95% CI = .78-1.15).…”
Section: Introductionmentioning
confidence: 88%
“…This is despite the slightly increased risk of COVID-related deaths in PWE. 6 All-cause deaths (excluding COVID-19 deaths) for PWE (and the whole Welsh population) reduced during the pandemic. This reduction in non-COVID-19 deaths during the pandemic has been found in other (but not all) populations.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation